Astronomy and the spiral of scientific culture (Seminário Internacional de Informação, Tecnologia e Inovação, 2025)
This study maps the activities of astronomical communities in Alagoas using the scientific culture spiral model. The research adopts a qualitative, descriptive, and exploratory approach, based on participant observation, interviews, and documentary research. The initiatives, actors, and institutions identified were organized into the following groups: production and dissemination of science and scientist training; teaching of and for science; and science communication. The results reveal the diversity of fields in which astronomy manifests in the state, including universities, schools, observatories, planetariums, astronomy clubs, and independent communicators, highlighting significant interactions between institutions and amateur astronomers.